Audible pedestrian warning system using embedded system. (February 2023) - Nalini, T.; Sendil Velan, S.; Shanmuganathan, M.; Kajendran, K.; Radhakrishnan, P.
Abstract: Despite their low emissions, hybrid electric cars have caused concerns for the safety of other road users (pedestrians, cyclists, etc.). At low speeds (below 30 km/h), electric and hybrid cars are almost quiet, which poses a risk to pedestrians. This is particularly true for those who are more susceptible to harm, such as the visually handicapped. The primary goal of this project is to create a working prototype of a vehicle (robot) equipped with a pedestrian-detecting automated signaling system and speakers aimed towards the pedestrian. This enhances the vehicle's capacity for responding to its surroundings. The alert tone must also be fine-tuned so that it is audible but not obnoxious.